Workshop Penerapan SAP2000 Untuk Konsultan Perencana Di Kabupaten Padang Lawas Utara - Pohan, Rizky Febriani; Rambe, Muhammad Rahman (Universitas Multi Data Palembang, Fakultas Ilmu Komputer dan Rekayasa, 2023)
The problem that occurs is there are many planning consultants in North Padang Lawas Regency who are not proficient and skilled in applying SAP2000. Therefore, it is necessary to hold a workshop on the implementation of SAP2000 for planning consultants in North Padang Lawas Regency as a solution to the problem that occurs. The aim of this workshop is to improve participants' skills in analysis with SAP2000. The stages of implementing this workshop are: conducting a survey on SAP2000 mastery; make proposals based on survey results; planning the preparation of materials, modules, pre-test, post-test, attendance and schedule of community service activities; dividing the team's tasks in which the chairperson serves as a teacher for one hour then the members continue, while students prepare attendance, pre-test and post-test; make conclusions based on the results of the pre-test and post-test that have been carried out. The methods applied in this activity include: presentations, tutorials and practices, modules and questions and answers. Based on the results of community service activities that have been carried out, it can be concluded that the SAP2000 application workshop for planning consultants in North Padang Lawas Regency was able to improve the skills of participants (planning consultants) in analyzing with SAP2000 with an increase in the level of achievement of high mastery of the material from 53.33 % to 80%. This happened because it was supported by the high interest and enthusiasm of the participants to take part in the workshop and training before the workshop was held through the distributed modules.